Akuntabilitas Perizinan Penyelenggaraan Reklame Di Kabupaten Sidoarjo - Yollan Nofita Indriawati; Luluk Fauziah (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2018)
This study aims to elucidate and to describe inhibiting the accountability of advertise- ment permission in Sidoarjo regency. The methodology used in this study is qualitative by using observation and interview whereas data analysis technique is collecting, serving, reducing, and verifying data. The result of this study showed that the accountability of advertisement permission in Sidoarjo regency has not been maximal because occurring frequently delay on the realization of advertisement permission. In addition to, mecha- nisms of online serving often occurs trouble. Even it is free but they should pay the tax. The obstacle of the accountability of advertisement permission in Sidoarjo regency still there is scalpers and no commitment of the advertisement technician to do applicable assignment.